2006
DOI: 10.1096/fj.06-6474fje
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of post‐transcriptional regulation in the maintenance of a partial muscle phenotype by electrogenic cells of S.macrurus

Abstract: Electrocytes, the current-producing cells of electric organs (EOs) in electric fish, are unique in that they derive from striated muscle and they possess biochemical characteristics of both muscle and non-muscle cells. In the freshwater teleost Sternopygus macrurus, electrocytes are multinucleated cells that do not contract yet retain expression of some proteins common to skeletal muscle cells. Given the role that transcriptional regulation plays in the activation of the myogenic program in vertebrates, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 52 publications
2
26
1
Order By: Relevance
“…For each specimen, the caudal peduncle or ~1cm of axial muscle posterior to the operculum and dorsal to the lateral line was removed and flash frozen in liquid nitrogen-chilled isopentane (Cuellar et al, 2006), then mounted on a dry ice-chilled chuck using Cryo-M-Bed (Bright Instrument Company, Huntingdon, UK). Tissues were cut at 20m using a cabinet cryostat onto freshly subbed slides and dried overnight at room temperature.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…For each specimen, the caudal peduncle or ~1cm of axial muscle posterior to the operculum and dorsal to the lateral line was removed and flash frozen in liquid nitrogen-chilled isopentane (Cuellar et al, 2006), then mounted on a dry ice-chilled chuck using Cryo-M-Bed (Bright Instrument Company, Huntingdon, UK). Tissues were cut at 20m using a cabinet cryostat onto freshly subbed slides and dried overnight at room temperature.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…For the purposes of later discussion, we assigned putative functional roles based on the known function of these genes in skeletal muscle: transcription factor, Ca 2+ binding, sarcomeric proteins, ion pump and other (Fig.2) Spatial distribution of proteins is similar but not identical between SM and EO Cuellar and colleagues described the existence of several mRNAs present in the EO of gymnotiforms (Cuellar et al, 2006), but their corresponding proteins were not found using either immunohistochemistry or western blotting, suggesting the existence of a post-transcriptional mechanism of regulating gene expression. Given the similar identities of the mRNAs detected by Cuellar and colleagues (Cuellar et al, 2006) and the differentially expressed ESTs described in this study, we wished to determine whether protein products like those differentially expressed ESTs described above were translated in mormyrid EO. We determined protein presence and distribution in the mormyrid EO and SM using widely cross-reactive antibodies for a subset of seven proteins: MHC, Na…”
Section: Identification Of Differentially Expressed Transcripts Betwementioning
confidence: 99%
See 2 more Smart Citations
“…We use this model system because skeletal muscle cells of electric fish express a unique ability to undergo changes in their biochemical and morphological properties and give rise to electrocytes, the current-producing cells of the electric organ (Bennett, 1971;Fox and Richardson, 1978;Fox and Richardson, 1979), and we have begun to determine how the developmental program for striated muscle has been altered to produce an electrogenic, noncontractile cell that retains a partial muscle phenotype Zakon and Unguez, 1999;Unguez and Zakon, 2002;Kim et al, 2004;Kim et al, 2008;Cuellar et al, 2006). We have exploited the inexhaustible regenerative capacity of adult S. macrurus to study the effects of neural input on the differentiation of muscle fibers and their phenotypic conversion into electrocytes.…”
Section: Skeletal Muscle and Electric Organ Regeneration In The Longtmentioning
confidence: 99%